The Effect of Transformational Leadership and Adhocracy Organizational Culture on Organizational Commitment with Work Engagement as A Mediating Variable in Digital Start-Up Employees - Amalina, Fildzah; Syaebani, Muhammad Irfan (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2025)
Leadership and culture plays an important role in attracting and retaining employees, especially the dominant organizational culture found in startups is adhocracy culture. The purpose of the study is to explain the effect of transformational leadership and adhocracy culture in digital startup companies on organizational commitment and examine the mediating effect of job attachment in this relationship. This study uses a quantitative approach to examine the influence of transformational leadership and adhocracy culture on organizational commitment with work engagement as a mediating variable. Data were collected from 256 digital startup employees in Indonesia through a closed questionnaire using a 1–6 Likert scale. The research instruments included GTL, OCAI and scales. Validity was tested using KMO, and reliability was assessed using Cronbach’s Alpha. Data analysis was conducted using Structural Equation Modeling (SEM) with LISREL 8.8 software. The results showed that job attachment affects organizational commitment as well as being a mediating variable that can affect the relationship between transformational leadership and adhocracy culture on organizational commitment of digital startup employees. These findings can be used to improve organizational commitment by exploring more deeply the use of transformational leadership and adhocracy culture that lead to work engagement and improve employee engagement.